Navigating Precision Medicine Within European Law: Ethical Considerations and Legal Challenges - Vlachothanasi, Eleni (Bioethica, 2024)
Precision medicine, characterized by personalized treatment strategies based on extensive patient-specific data, has gained prominence in recent years. This paradigm shift from the traditional one-size-fits-all approach aims to optimize healthcare outcomes by integrating genomic, clinical, and lifestyle information. While precision medicine’s transformative impact in fields like oncology and pharmacogenomics is evident, regulatory frameworks, including GDPR, Clinical trials regulation, IVD regulation, and the recently effective Health Technology Assessment Regulation (HTAR) from January 2025, are scrutinized for their contributions and identified gaps. Despite significant progress, challenges persist, including issues related to informed consent, companion diagnostics, direct-to-consumer genetic tests, intellectual property rights, and diverse healthcare policies across the EU. The lack of global harmonization adds complexity to regulatory environments. The conclusions stress the dynamic nature of precision medicine, proposing proactive measures such as the establishment of multidisciplinary committees within the EU to adapt swiftly to emerging advancements and ensure seamless integration into healthcare systems. This symbiotic relationship between precision medicine and European law reflects a commitment to creating an environment where cutting-edge medical technologies can thrive, contributing to a healthier and more resilient population through ongoing efforts to refine legal frameworks.